Fixation vs Arthroplasty for Femoral Neck Fracture in Patients Aged 40-59 Years: A Propensity-Score-Matched Analysis - Jacob M. Wilson, MD; Corey A. Jones, MD; Jeffrey Scott Holmes, MD; Kevin X. Farley, BA; Roberto C. Hernandez-Irizarry, MD; Thomas J. Moore, Jr., MD; Thomas L. Bradbury, MD; George N. Guild, MD (Arthroplasty Today, 2022)
Background: Internal fixation (IF) has historically been favored for the treatment of femoral neck fractures (FNFs) in young, nongeriatric patients. However, recent literature reporting high reoperation rates among those receiving IF, taken in conjunction with favorable survivorship of modern bearing surfaces in total hip arthroplasty (THA), has begun to question this paradigm. Our study sought to compare outcomes between IF and THA for FNFs in patients aged 40-59 years. Methods: Using the Truven MarketScan Database, we performed a retrospective propensity-score-matched cohort study on patients aged 40-59 years who underwent surgical management of an isolated FNF (THA or IF). Patients with pathologic fracture were not included. Analysis was conducted on patients aged 40-49 and 50-59 years separately. A subgroup analysis was performed on those patients with 1 year and 3 years of follow-up. Multivariate analysis, controlling for baseline patient information, was then performed. Results: Seven hundred sevety-eight 40- to 49-year-old patients and 3470 50- to 59-year-old matched patients (IF and THA) were included in this study. A multivariate analysis found that patients aged 40-49 years who underwent IF were at higher odds of both 1-year (odds ratio 2.35, 95% confidence interval 1.22-4.54, P = .011) and 3-year (odds ratio 5.68, 95% confidence interval 2.21-14.60, P < .001) reoperation. Similar results were found in those aged 50-59 years. While complication rates were similar, postoperative anemia and 90-day visits to the emergency room were more common after THA in both age cohorts. Conclusions: While THA is associated with increased postoperative anemia and resource utilization compared with IF, patients aged 40-59 years who undergo IF for FNF are at increased risk of reoperation in the first 3 postoperative years. This information should be used to assist in shared decision-making with patients in this age group.